PEMBELAJARAN MEMBACA PERMULAAN DENGAN PERMAINAN BAHASA DI KELAS AWAL SD/MI - Mustofa, Mustofa (Jurnal Bahasa Lingua Scientia, 2011)
Early reading constitutes one of the steps in Reading teaching and learning process for the first grader of Elementary School/Madrasah Ibtidaiyah. The students read to acquire and master the reading technique as well as the information in the reading text. Therefore, the teacher must plan the Reading lesson well in order that the students will be able to accustom themselves to a good and fun reading habit. The learning atmosphere must be developed through fun language activities. Such kinds of activities are in accordance to children?s characteristics, who like to play. Playing possesses a significant role in the children?s cognitive and social development.